Periodontal Disease, Inflammatory Cytokines, and PGE2 in Pregnant Patients at Risk of Preterm Delivery: A Pilot Study - Catalina Latorre Uriza; Juliana Velosa-Porras; Nelly S. Roa; Stephani Margarita Quiñones Lara; Jaime Silva; Alvaro J. Ruiz; Francina Maria Escobar Arregoces (Hindawi Limited, 2018)
Periodontal disease is an infection that, in pregnant women, can act as a risk factor for preterm delivery by increasing local and systemic inflammatory responses. Objective. To analyze the presence of periodontal disease, proinflammatory cytokines, and prostaglandin E2 (PGE2) in pregnant patients at high risk for preterm delivery. Materials and Methods. Pilot study for a case-control study. We included 46 pregnant patients (23 patients at risk of preterm delivery as cases and 23 patients without risk of preterm delivery as controls). We excluded patients who received periodontal treatment, antibiotics, or antimicrobials over the last 3 months as well as those with infections or diseases such as diabetes or hypercholesterolemia. The patients underwent a periodontal assessment, and their levels of cytokines (interleukin- [IL-] 2, IL-6, IL-10, and tumor necrosis factor- [TNF-] α) and prostaglandin E2 (PGE2) were quantified. Results. Patients with periodontal disease showed higher levels of cytokines (IL-2, IL-6, IL-10, and TNF-α) and PGE2. Patients at high risk for preterm birth showed higher IL levels compared with patients at low risk for preterm delivery. PGE2 increased with the severity of periodontal disease. PGE2 was higher in patients at low risk for preterm delivery, although this difference was not significant. Conclusion. Periodontal disease can increase the systemic inflammatory response as well as the levels of PGE2 and inflammatory cytokines in pregnant patients.